Let's get invisible! - Stine, R. L. (New York, NY : Scholastic Inc., 2015)
When a magic mirror holds twelve-year-old Max invisible for too long, he fears that he may be changed forever by a reflection of his real self.
4.0
5-8.
5-8
Keywords: Mirrors -- Juvenile fiction; Reality -- Juvenile fiction; Horror stories; Mirrors -- Fiction; Reality -- Fiction; Horror fiction; Mirrors -- Fiction; Reality -- Fiction; Horror fiction